Faktor-Faktor Yang Mempengaruhi Produksi Industri Kecil Sulaman di Provinsi Sumatera Barat - Aninda Aizat; Sri Ulfa Sentosa (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study.aim to examine of the factors that influence the production of small embroidery industries in West Sumatra Province with the Fixed Effect Model (FEM) selected. The data used is panel data during the 2014-2018 period, with documentation data collection techniques and literature study obtained from related institutions and agencies. The variables used are Capital (X1), Labor (X2) and Business Units (X3). The research method used is:  OLS.  estimation results show the capital has positive, insignifican. Effect.on embroidery production in West Sumatra. Furthermore, Labor has a negative and insignificant effect on embroidery production in West Sumatra. And the business unit has a positive and significant effect on embroidery production in West Sumatera. Together., capital, labor and business units have a significant effect on embroidery production in West Sumatra.